HST hot-Jupiter transmission spectral survey: haze in the atmosphere of WASP-6b. Issue 1 (17th December 2014) - Nikolov, N.; Sing, D. K.; Burrows, A. S.; Fortney, J. J.; Henry, G. W.; Pont, F.; Ballester, G. E.; Aigrain, S.; Wilson, P. A.; Huitson, C. M.; Gibson, N. P.; Désert, J.-M.; et al.
Abstract : We report Hubble Space Telescope optical to near-infrared transmission spectroscopy of the hot-Jupiter WASP-6b, measured with the Space Telescope Imaging Spectrograph and Spitzer's InfraRed Array Camera. The resulting spectrum covers the range 0.29–4.5 μm. We find evidence for modest stellar activity of WASP-6 and take it into account in the transmission spectrum. The overall main characteristic of the spectrum is an increasing radius as a function of decreasing wavelength corresponding to a change of Δ ( R p / R * ) = 0.0071 from 0.33 to 4.5 μm. The spectrum suggests an effective extinction cross-section with a power law of index consistent with Rayleigh scattering, with temperatures of 973 ± 144 K at the planetary terminator. We compare the transmission spectrum with hot-Jupiter atmospheric models including condensate-free and aerosol-dominated models incorporating Mie theory. While none of the clear-atmosphere models is found to be in good agreement with the data, we find that the complete spectrum can be described by models that include significant opacity from aerosols including Fe-poor Mg2 SiO4, MgSiO3, KCl and Na2 S dust condensates. WASP-6b is the second planet after HD 189733b which has equilibrium temperatures near ∼1200 K and shows prominent atmospheric scattering in the optical.